Adherence of Public Officials to the Disclosure of Conflict of Interest While Performing Their Job Responsibilities: A Comparative Study between French and Jordanian Law - Al-Zu’bi, Hadeel Tayseer Mahmoud (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to analyze the legal framework regarding the duty of public officials to disclose conflicts of interest and draw lessons from the French experience. It identifies legislative gaps in Jordanian laws concerning the duties of public officials, the nature of conflicts of interest, and the mechanisms for disclosure during and after service. Methods: This study utilized a descriptive, analytical, and comparative approach. It presented relevant legal texts defining the responsibilities of public officials, clarified the nature of conflicts of interest and their cases, analyzed and interpreted their content, and compared them with French law. Results: The prevalence of conflicts of interest can be attributed to the lack of awareness among public officials due to the omission of a mechanism for mandatory disclosure and effective methods to confront these conflicts in Jordanian legislation. Furthermore, administrative control over public officials has not been adequately activated. Conclusions: Legislative frameworks, both preventive and precautionary, are necessary to regulate the disclosure of conflicts of interest in public service. The study recommends adopting the French approach by establishing an independent administrative authority dedicated to public transparency. This authority would declare and publish employees’ interests, prevent conflicts of interest, disclose, and mitigate their cases, and enhance transparency between citizens and the administration.